MANAJEMEN PROGRAM BILINGUAL BERBASIS PENDIDIKAN HOLISTIK DI SMA MUHAMMADIYAH 1 PONOROGO - Ita Yuli Kadarwati; Miftahul Ulum (Excelencia: Journal of Islamic Education & Management, 2021)
Holistic education strives for students to be able recognize, understand, analyze, and make connections between one subject and other. SMA Muhammadiyah 1 Ponorogo as an islamic education institution that promotes holistic education, carrier out bilingual program management. Basically, the bilingual program is needed to equip educator and students to have global competitiveness due to their proficiency in english. Thus, this study aims to analyze planning, implementation, evaluation, and to find out what obstacles are involved when implementing a holistic education based bilingual program. The type of this research is qualitative research with a case study approach on how to manage bilingual programs at SMA Muhammadiyah 1 Ponorogo. The result of this study are: (1) bilingual program planning includes the preparation of the learning curriculum, the preparation of teaching staff, and development work plans and programs, (2) the implementation of the related bilingual program regarding the applied teaching metho, namely integrated learning where students will analyze the interrelationship between subject, in addition to developing english language skills teaching educators to use english at the opening,closing, and reviewing the previous material, (3) evaluating the bilingual program using report cards, english camp and TOEFL certificates, and the number of students who have successfully studied at hoe (well-knwn private and public universities) and abroad, and (4) the obstacles faced during the implementation of the bilingual program are that educators have not been actively using english when teaching which in the end has an impact on the difficulty of students